A bill to incorporate the Atlantic and North Carolina Railroad Company (House doc. (North Carolina. General Assembly. House of Commons) ;)
1852 North Carolina House bill and its amendments regarding the incorporation of the Atlantic and North Carolina Railroad Company. The railroad would be constructed between the towns of Goldsboro, Wayne County and Beaufort, Carteret County. Included were the subscription procedure, appointment of the commissioners, officers, and directors, as well as all corporate matters, powers, duties and obligations. Of note, section XLIV allowed for free transportation of troops and munition of war when the state faced "domestic invasion or insurrection."